2007
DOI: 10.1021/es062256w
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Outflow of Anthropogenic Semivolatile Organic Compounds from East Asia in Spring 2004

Abstract: To estimate the emissions of anthropogenic semivolatile organic compounds (SOCs) from East Asia and to identify unique SOC molecular markers in Asian air masses, high-volume air samples were collected on the island of Okinawa, Japan between 22 March and 2 May 2004. Contributions from different source regions (China, Japan, the Koreas, Russia, and ocean/local) were estimated by use of source region impact factors (SRIFs). Elevated concentrations of hexachlorobenzene (HCB), hexachlorcyclohexanes (HCHs), dichloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(144 citation statements)
references
References 27 publications
3
139
2
Order By: Relevance
“…This phenomenon demonstrates that SCCPs were mainly influenced by local sources, even though other POPs in the atmospheres of Japan and South Korea have been shown to be affected by sources in China to a certain extent. 29,30 The calculated characteristic travel distances (CTD) of SCCPs, calculated using the OECD software tool, were approximately 600−900 km. 31 This relatively low long-range atmospheric transport potential could explain the observations of this present study.…”
Section: Spatial Distribution and Seasonal Variations The Spatial DImentioning
confidence: 99%
“…This phenomenon demonstrates that SCCPs were mainly influenced by local sources, even though other POPs in the atmospheres of Japan and South Korea have been shown to be affected by sources in China to a certain extent. 29,30 The calculated characteristic travel distances (CTD) of SCCPs, calculated using the OECD software tool, were approximately 600−900 km. 31 This relatively low long-range atmospheric transport potential could explain the observations of this present study.…”
Section: Spatial Distribution and Seasonal Variations The Spatial DImentioning
confidence: 99%
“…The model results were compared with the observations at six monitoring sites including Changdao, Gosan, Kanazawa, Okinawa, Cheeka Peak Observatory (CPO), and Mount Bachelor Observatory (MBO) during different time periods when observations were actually conducted (Feng et al, 2007;Lee et al, 2006;Tamamura et al, 2007;Primbs et al, 2007;Killin et al, 2004;Primbs et al, 2008). A map of the location of these sites as well as a comparison of their measured concentrations is shown in Fig.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…Many studies dedicated to investigating the episodic nature of transpacific transport indicate stronger transport of pollutants than background level under certain meteorological conditions (Lee et al, 2006;Tamamura et al, 2007;Primbs et al, 2007;Killin et al, 2004;Primbs et al, 2008). Transformation (ITCT 2K2) experiment was conducted over the West Coast of North America, and air masses containing pollutants originating from Asia were measured by aircraft over a region bounded by 32-44 • N, 122-125 • W, and 0-8 km altitude (Allan et al, 2004).…”
Section: Episodic Transport Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…For both DDTs and HCHs, passive air sampling (Jaward et al, 2005) and back trajectory simulation of air masses (Primbs et al, 2007) showed that the PRD was one of the regions in East Asia that possessed the highest levels with elevated atmospheric outflows. Generally, almost all mean concentrations of DDTs in urban, suburban, and rural areas of the PRD were significantly higher than those observed at a rural site in Hong Kong (Table 1).…”
Section: Airmentioning
confidence: 99%